2018
DOI: 10.1515/gps-2016-0138
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of iron oxide nanoparticles in a continuous flow spiral microreactor and Corning® advanced flow™ reactor

Abstract: Abstract:In the present work, synthesis of iron oxide nanoparticles (NPs) using continuous flow microreactor (MR) and advanced flow™ reactor (AFR™) has been investigated with evaluation of the efficacy of the two types of MRs. Effect of the different operating parameters on the characteristics of the obtained NPs has also been investigated. The synthesis of iron oxide NPs was based on the co-precipitation and reduction reactions using iron (III) nitrate precursor and sodium hydroxide as reducing agents. The ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 64 publications
(67 reference statements)
1
13
0
Order By: Relevance
“…Meanwhile, the high temperature had a significant impact on the formation of the Fe 2 Ni‐BDC crystal at 180 °C. The XRD result illustrated that there appear some diffraction peaks at 2 θ of 31.8°, 33.1°, 35.1°, 45.2°, and 46.1° suitable with some metal oxides as Fe 2 O 3 (220), Fe 2 O 3 (104), Fe 2 O 3 (110), NiO(200), and Fe 2 O 3 (400) 48–50, 52–54. These results showed that the MOF materials could generate metal oxides when synthesized at high temperature.…”
Section: Resultsmentioning
confidence: 98%
“…Meanwhile, the high temperature had a significant impact on the formation of the Fe 2 Ni‐BDC crystal at 180 °C. The XRD result illustrated that there appear some diffraction peaks at 2 θ of 31.8°, 33.1°, 35.1°, 45.2°, and 46.1° suitable with some metal oxides as Fe 2 O 3 (220), Fe 2 O 3 (104), Fe 2 O 3 (110), NiO(200), and Fe 2 O 3 (400) 48–50, 52–54. These results showed that the MOF materials could generate metal oxides when synthesized at high temperature.…”
Section: Resultsmentioning
confidence: 98%
“…The obtained nanoparticles are known for their narrow size distribution, uniform shape, improved reproducibility, shorter reaction time, increased yield-formation of pure phase magnetite, and friendly reaction conditions with no extra additives or heating. However, since the field of microfluidics as applied to nanomedicine is still in its infancy, there are several drawbacks associated with this method, namely: surface roughness, limited production rate, possibility of clogging micro-channels, leaks-leading to experimental failure, capillary force and chemical interactions [48,49].…”
Section: Other Used Methodsmentioning
confidence: 99%
“…T-junction, Y-mixing, capillary, coaxial tubes and different designs of static micromixers are also utilized as microreactors in microfluidic particle formation processes. The phase-homogeneity offers reliable control of reaction parameters, such as temperature and reaction time, which makes continuous microfluidic synthesis suitable for both non-magnetic [67,70], as well as for magnetic nanoparticle production [71][72][73]. Furthermore, the technique is capable for multi-step syntheses and the subsequent modification of the product [74].…”
Section: Microfluidic Synthesismentioning
confidence: 99%